ESD and Pit Pattern Diagnosis: Lessons from a Japanese Endoscopist Working in the United States - Nishimura, Makoto (Clinics in Colon and Rectal Surgery, 2020)
Endoscopic submucosal dissection (ESD) was developed in 2000s to overcome the limitations of endoscopic mucosal resection (EMR), especially to accomplish en-bloc resection, and it has been accepted worldwide in the past decades. Many ESD devices and diagnosis modalities are currently available, which include pit pattern and narrow band imaging (NBI) diagnoses to evaluate the depth of the tumor preoperatively with sensitivities of 70 to 90%. Depending on the Japanese colorectal guideline, the intramucosal cancer and shallow invasion of the submucosal layer are the main good indications of ESD; however, the ESD practices between Japan and Western countries still vary, including pathologic definition of cancer, tumor/node/metastasis classification, and handling of ESD specimen. In the United States, despite the large demand for treatment of colorectal neoplasm, pit pattern and magnified NBI diagnoses are not widely accepted yet, and piecemeal EMR is still the major method in most of the institutions. Moreover, the specific guideline of ESD is also not available yet. More new technologies are being developed other than conventional ESD methods in Eastern and Western countries, and ESD is now expected to change in the next generation. It is recommended that not only gastroenterologists but also colorectal surgeons have appropriate knowledge of colorectal lesions and their management to ensure current treatments is applied to patients.
Keywords: ESD; Kudo's pit pattern; JNET classification; traction device